Multilevel marketing: pyramid-shaped schemes or exploitative scams? - Yair Antler (Theoretical Economics, 2023)
Motivated by the growing discussion on the resemblance of multilevel marketing schemes to pyramid scams, we compare the two phenomena based on their underlying compensation structures. We show that a company can design a pyramid scam to exploit a network of agents with coarse beliefs and that this requires the company to charge the participants a license fee and pay them a recruitment commission for each of the people that they recruit and that their recruits recruit. We characterize the schemes that maximize a company's profit when it faces fully rational agents, and establish that the company never finds it profitable to charge them a license fee or pay them recruitment commissions.
Keywords: D84; D86; L29; 330; analogy-based expectations; misspecified models; Multilevel marketing; pyramid schemes; speculative trade